Blockchain technologies for leveraging security and privacy - Vassilakis, Costas (Homo Virtualis, 2019)
The contemporary internet has developed into a complex ecosystem involving humans, services, applications, machines and applications that interact exchanging information, ranging from e-mail messages and social media content to crowdsourcing data and videoconferencing. In this context, a number of security threats such as viruses and malware exist, while additionally the users’ privacy is jeopardized by threats such as personal data leakage, usage pattern monitoring, and so forth. The IoT trend renders the Internet ecosystem even more complex, by adding a rich set of services, applications and machines, many of them backed by new user roles; these elements are weaved into everyday life and industry alike. This increases both the number of opportunities available to threat agents for exploitation and the volume and value of the underlying infrastructure and data, increasing thus the user risk level. In this paper, we explore how the Blockchain technology can be used to leverage security and privacy in the modern Internet, both by providing underpinnings for preventive measures and by facilitating digital forensic evidence collection storage, safeguarding and controlled access.